Strategi Pembentukan Karakter Disiplin dan Tanggung Jawab Siswa Melalui Kegiatan Ekstrakurikuler Pramuka di SDN Komplek Kenjeran II/506 Surabaya - Salsabiila, Iffah; Djazilan, Syukron; Rahayu, Dewi Widiana; Sunanto, Sunanto (CV Insan Kreasi Media, 2023)
Scout extracurriculars provide an important role in a process of forming student character. Scout extracurricular is one of the extracurricular activities that is present as a vehicle in the formation of student character. The purpose of this study is to analyze, describe and find out strategies for building the character of discipline and student responsibility through scout extracurricular activities at SDN Komplek Kenjeran II/506 Surabaya. This research method uses a qualitative approach. Data collection techniques are carried out by observation, interviews, and documentation. The targets in this study were scout coaches, scout members and school principals. The results of the study showed that there was an influence in the implementation of the strategy for building the character of discipline and student responsibility through scout extracurricular activities at SDN Komplek Kenjeran II/506 Surabaya. This can be proven by the achievement of indicators of discipline and responsibility. Discipline in using time, participating in religious events according to their religion, participating in scout extracurricular activities, dressing neatly, using complete attributes, obeying the rules. Responsibilities in implementing and leading team discussions, operating and maintaining technology, leading and training squadrons and proposing problem solving. Keywords : Character, Extracurricular, Discipline, Responsibility